From Innovation to Ethics: Guidelines for the Use of Artificial Intelligence in the Legislative (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2025)
The use of LLM to generate legal texts presents both opportunities and risks. By examining white-box models, model explainability, target audiences, and alternative scenarios, we can identify the technical and strategic considerations necessary for their ethical use by respecting equal treatment, truthfulness, privacy, responsibility and legality. This analysis informs a proposed strategy for leveraging generative artificial intelligence in legislative contexts.
Keywords: Artificial intelligence; ethics; legislation; parliaments; language models